Proposição de soluções de esgotamento sanitário em comunidades rurais do Estado de Goiás - Vale, Gabrielle Brito do (2022)
Surveys show how sewage coverage in rural communities is mostly characterized by its precariousness or lack of solutions throughout Brazil, with rudimentary septic tanks being used in the State of Goiás by 60 to 80% of the rural population (BRASIL, 2019). This framework contributes to the emergence of environmental risks and to the health of populations. To improve this situation, according to article 3-B of Federal Law 14026 of July 15, 2020, which updates the legal framework for sanitation, individual and collective sewage services involve the treatment unit and the alternative management sludge, which must be disposed of in an environmentally appropriate manner, including septic tanks. These units are the most suitable alternatives currently used in rural areas, and are characterized by producing sludge, which when poorly managed harms the treatment and environment, making the study of its management relevant. Furthermore, solutions for sewage treatment can be applied according to the effluent generated in the rural household, and analysis of the possibility of integrating treatment with animal manure management and practiced agriculture. Thus, the objective of this work is to propose solutions for the treatment of sanitary sewage and sludge management in rural communities in the State of Goiás. To this end, a survey was carried out on the service in 113 communities in the State of Goiás, including riverside communities, quilombolas and settlements, diagnosed in the Environmental Sanitation and Health Project (SanRural). the need for animal manure for the technologies to work, or plantations for the application of the treated effluent, in order to allow its reuse in agriculture/plantations and the management of animal manure together with the treatment. Technological groups were elaborated for proposition, being: A and D (with restrictions only on the type of effluent), B (with planting and manure needs) and C (planting needs). For the sludge management solutions, individual management modalities (exclusively and shared) and collective management without analytical control and with (analysis of the quality of the effluent and receiving body) were considered, and how these would impact the operational and maintenance costs of tanks septic, varying the amount of population served from 20 to 2000 inhabitants. From the results, it was observed that the service in the communities was characterized by a high deficit in all typologies. The proposition of solutions indicated the greater applicability of the technologies of group A and D in all typologies. Those in group B were more applicable in settlements, where there is a greater presence of plantations and animal manure. In general, all propositions pointed to solutions that allow the adequate treatment of effluents, feces and urine, which can contribute to the promotion of environmental health. As for sludge management, based on the per capita costs of the solutions, it was identified that: shared individual management is more applicable in communities, and collective management can be favored in the absence of analytical control. Therefore, it is concluded that it is possible to apply several solutions for the treatment of sewage, which can contribute to agricultural production, environmental quality and management of animal manure. In general, shared individual management had the lowest cost, however, the participation of different sectors of society and public authorities is important.